Comparative Study: Understanding the Visual Identity of Batik Brands in Indonesia - El Chidtian, Aileena Solicitor Costa Rica; Arifianto, Pungky Febi; Renzina, Yudha Delonix (DeKaVe, 2024)
This research is a comparative study of the visual identity of batik brands in Indonesia, which aims to identify the differences and similarities in the visual elements of various leading batik brands. Brand visual identity is an important aspect of marketing efforts, because it reflects the image and values that a company wants to convey to consumers. In the context of batik, which is Indonesia's cultural heritage, visual identity is becoming increasingly important as a way to maintain traditional values while remaining relevant in the modern market. The aim of this research is to understand the meaning and dynamics behind the visual identity of a batik brand. This research analyzes the visual symbols of 4 leading batik brands in Indonesia which are analyzed and compared with each other using a qualitative comparative analysis method. The research results show that although many batik brands emphasize traditional elements in their visual identity, there is significant variation in how these brands adapt modern elements to appeal to different market segments. Some brands emphasize traditional motifs with natural colors, while others combine contemporary elements to create a more modern and minimalist impression. Additionally, it was found that brands that focus more on international markets tend to adopt a more universal and simple visual style, compared to brands that focus more on the domestic market which often maintain local uniqueness in their designs